ATMPH 2020
DOI: 10.36295/asro.2020.231615
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of pilB gene in Pseudomonas aeruginosa isolated from Iraqi patients with burn infections

Abstract: In this study out of 50 isolates of burns infections only 15(30%) was identified as Pseudomonas aeruginosa depending on selective media, morphological and biochemical tests then confirmed by using VITEK-2 Compact system. The pilB virulent gene was present in 15 (100%) isolates depending on PCR by using specific primers of pilB gene (826bp). The nucleotides pilB sequence has been done to nine isolate, Results displayed occurrence of some substitution gene mutations from (100-90.05%) identity with the reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Previous studies suggested that these isolates' inability to build biofilm was caused by conformational changes in quorum sensing (RhlR) proteins mediated by mutations in the rhlI/rhlR system 27,42 . However, the present results go with the results of another investigation which showed a strong connection between the ability to create biofilms and the presence of pertinent genes 2,43 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies suggested that these isolates' inability to build biofilm was caused by conformational changes in quorum sensing (RhlR) proteins mediated by mutations in the rhlI/rhlR system 27,42 . However, the present results go with the results of another investigation which showed a strong connection between the ability to create biofilms and the presence of pertinent genes 2,43 .…”
Section: Discussionsupporting
confidence: 91%
“…Pseudomonas aeruginosa (PA) is one of the most common nosocomial pathogens in Iraqi hospitals that can cause serious infections with fatal complications 1,2 . The constant misuse and abuse of antibiotics for treating the infections resulted in the widespread development of multi-drug resistant (MDR) strains and complicated medical therapy against P. aeruginosa [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas aeruginosa isolates were obtained from clinical sources of burn injuries and were identified and activated on nutrient agar according to Shehab et al 15 . As for the probiotic isolates, which include L. acidophilus and S. boulardii were obtained as identified isolates from the microbiology laboratory of the College of Science for Girls / University of Baghdad, and they were activated and cultured on MRS broth and Sabrouraud agar, respectively, according to Rezuqi and Younis 16 , and then kept in the refrigerator until use.…”
Section: Bacterial Isolatesmentioning
confidence: 99%